Factors Affecting Effective Teaching Of Chemistry Lessons:The Case Of Preparatory Schools In East Shoa Zone. - Muliye Moges (ASTU, 2018)
The purpose of this study was to investigate the factors that affect effective teaching of chemistry lessons in selected preparatory schools found in East Shoa Zone, in the Oromia Regional State. The study used descriptive survey research design and simple random sampling technique for students and available sampling technique for teachers and school administrators. The sample consisted of 368 respondents; from these 340 were students, 20 were chemistry teachers and 8 were school administrators from four preparatory schools. The instruments used for data collection were an open-ended and close-ended questionnaire, semi-structured interview and focused group discussions. The questionnaire used was framed in the form of five-point Likert scale (strongly agree, agree, not sure, disagree, and strongly disagree) and it was administered to 340 students and 20 teachers. The relationship between the students and teachers responses to these factors was carefully examined. The collected data were analyzed using mixed approaches of data analysis. The quantitative data were analyzed using mean, standard deviation and t-test using SPSS package. The result showed that there is significance relationship negatively and positively in the responses of students and teachers to some of the factors that affect effective teaching of chemistry. The factors were teachers’ competency, teachers’ attitude towards teaching chemistry, students’ attitude towards learning chemistry, the impact of educational leaders or directors on the effective teaching of chemistry, appropriateness of the curriculum prepared for the level, the impact of class size, availability of adequate facilities and the impact of societal attitude on the effective teaching of chemistry. Thus, some suggestions were offered on how educational leaders managed the schools, and school community involved could improve the factors highlighted to make the teaching and learning of chemistry more effective and efficient
The Case Of Preparatory Schools In East Shoa Zone.